KONSEP KEPEMIMPINAN PENDIDIKAN DALAM MENGEMBANGKAN PRINSIP PEMBERDAYAAN MASYARAKAT - Marjuni, H.A. (Inspiratif Pendidikan, 2021)
Leadership is the process of inspiring others to work hard to achieve important work. Leadership builds commitment and enthusiasm for people to carry out their talents to help achieve plans, supervision so that things go well. In its activities, the leader has the power to mobilize and influence his subordinates in relation to the tasks that must be carried out. At the assignment stage, the leader must provide clear direction and guidance, so that subordinates can carry out their duties easily and the results are achieved in accordance with the objectives that have been set. Conceptually, the term empowerment has the basic word "power" which means ability, strength, ability to do business. Empowerment in education can be interpreted as a process of making human resources capable or strong in carrying out an effort in a certain field in the field of education The goal of community empowerment is to help people gain the power to make decisions and determine the actions they will take related to themselves , including reducing the effects of personal and social barriers to action